Rethinking Artificial Intelligence in Islamic Education: Ethics, Scholarly Authority, and Learning Transformation - Mellia Ristika; Yeni Sulastri (Suria Academic Press, 2026)
The rapid advancement of Artificial Intelligence (AI) has fundamentally transformed the educational landscape, including Islamic education. While AI offers significant opportunities to enhance learning through personalized instruction, adaptive assessment, and more efficient academic services, it also raises critical concerns related to ethics, academic integrity, information validity, and the shifting of scholarly authority. This study aims to conceptually examine the ethical challenges, the transformation of scholarly authority, and the changing learning practices associated with AI implementation in Islamic education, while proposing a conceptual framework to support its ethical and value-based integration. The study employs a conceptual research design using a critical literature analysis approach by synthesizing findings from peer-reviewed journal articles, academic books, and policy documents on AI and Islamic education. The analysis involves concept identification, thematic categorization, critical evaluation, and conceptual synthesis. The findings indicate that AI can improve learning effectiveness and educational innovation; however, its implementation should be guided by robust ethical governance, academic integrity, reliable knowledge validation, and the preservation of teachers' pedagogical and moral authority. As its primary contribution, this study proposes the Islamic Ethical AI Learning Framework (IEALF), which integrates AI, educators, learners, and Islamic values based on the principles of amanah (trustworthiness), 'adl (justice), maslahah (public benefit), and ta'dib (ethical cultivation). The proposed framework provides a conceptual reference for educational institutions in implementing AI responsibly while preserving the fundamental objectives of Islamic education.